EFEKTIVITAS PERLINDUNGAN HUKUM INDIKASI GEOGRAFIS "BIMA NTANDA RAWO" PASCA PENDAFTARAN STUDI TENTANG DAMPAK EKONOMI DAN TANTANGAN PENEGAKAN HUKUM: The Effectiveness Of Legal Protection For The Geographical Indication “Bima Ntanda Rawo” Post-Registration A Study On The Economic Impact And Law Enforcement Challenges - Aryani, Feni; Muthiah, Hanifah; Hamidah, Nur Khusnul (Ganec Swara, 2025)
This research is motivated by the urgency of legal protection for Geographical Indications (GI) regarding the “Bima Ntanda Rawo” woven fabric as an intangible cultural heritage and a source of economic welfare for the community in Bima. The main objective of this study is to examine the effectiveness of GI legal protection after registration, focusing on its economic impact on artisans and the challenges faced in enforcement. The research method employs a normative-sociological approach, combining doctrinal and legal norms analysis (Law No. 20/2016, Ministerial Regulations, and TRIPs) with empirical data from interviews and field observations with weaving artisans. The results show that GI legal protection has increased sale prices, added value, and product image, although its implementation still faces administrative, financial, and legal socialization obstacles. Legal enforcement of GIs also faces issues regarding proof of violations and weak legal literacy among artisan communities. These findings enhance understanding of community-based legal effectiveness and imply the need for institutional strengthening, a simple reporting system, and technological integration for GI supervision. The study’s limitation lies in the empirical data scope, which does not yet cover cross-regional cases, and the optimization of digital analysis for GI product surveillance